Medical imaging for cardiac regeneration using resident cardiac stem cells. (October 2013) - Choi, Sung Hyun; Yoo, So Young; Yoo, Sae Mi; Lee, Kyeong Been; Baek, Sang Hong; Kwon, Sang-Mo
Resident progenitor/cardiac stem cells (CSCs) are known to improve cardiac function through differentiation into cardiomyocytes and vascular lineages. To evaluate the effects of transplanted CSCs, appropriate imaging analysis modalities (e.g., optical imaging, MRI and radionuclide imaging) are required. However, the medical imaging modalities used for in vivo monitoring of transplanted CSCs may have distinct advantages and disadvantages. In this article, we will review the classification of CSCs and the imaging analysis methods developed thus far for use in CSC experiments. We will also discuss the direction of future medical imaging analysis strategies for CSC biology.